Comparison of the Effect of Vaginal Isosorbide Mononitrate and Estradiol on Cervical Ripening in Term Pregnancy: A controlled clinical trial - Giti Rahimi; Farhad Pourfarzi; Nasrin Fouladi; Nooshin Chamheidar; Samira Shahbazzadegan (Mashhad University of Medical Sciences, 2018)
Introduction:Cervical ripening usually starts before the onset of labor contractions and is necessary for dilatation and embryo passage. Considering the importance of vaginal delivery and reduction of cesarean risk, cervical ripening in pregnant women is a priority for Gynecology. Therefore, this study was performed with aim to compare the effects of isosorbide mononitrate and estradiol on cervical ripening and labor induction and the complications of these two drugs. Methods: This double-blind randomized clinical trial was performed in 2016 on 99 pregnant women over 40 weeks of gestation who referred to Alavi hospital in Ardabil. Participants were randomly allocated in to three groups of isosorbide mononitrate, estradiol and placebo. The tablet were placed in the posterior fornix, out-patiently. All three groups were hospitalized after 12 hours. Because of Bishop scores (BS) less than 6, the previous doses were repeated in all groups. Examination of the cervix was performed every 2 hours and blood pressure and heart rate of the mother were checked every 4 hours. Data were analyzed by SPSS software (version 16), one way ANOVA, Chi-square and Kruskal-Wallis tests. P <0.05 was considered significant. Results:The time of cervical ripening up to delivery was similar in Isosorbide and Estradiol groups (p=0.381), but it was significantly shorter in both groups than placebo group (p=0.016). Isosorbide and Estradiol also increased cervical Bishop Score. No significant difference was found between the groups in terms of duration of active phase of delivery (p=0.860). Despite of higher cesarean frequency in placebo group, no significant difference was observed between three study groups in terms of mode of delivery (p=0.484). The drug side effects were higher in Isosorbide and Estradiol groups compared to placebo. Conclusion: Isosorbide mononitrate and Estradiol changed Bishop Score as similar, and reduced the duration of ripening to delivery. Both drugs reduced the hospitalization time to delivery, cost of delivery induction, and improved delivery experience, without need to any aid instruments or surgery.